2018
DOI: 10.1590/s0100-83582018360100090
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthetic Potential and Productivity of Common Beans under Herbicide Effect

Abstract: The objective of this study was to evaluate the effects of the application of contact herbicides recommended for common bean crops, as for chlorophyll a fluorescence parameters, leaf soluble proteins content (LSPC) and productivity. The experiment was conducted on the field with five treatments, which were the application of the following herbicides: bentazon (720 g ha-1), fluazifop-p-butil (187.5 g ha-1), fomesafen (250 g ha-1) fluazifop-p-butil + fomesafen (187.5 + 250 g ha-1), and a manually weeded control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
1
0
0
2
Order By: Relevance
“…This inhibition of photosynthesis and oxidative stress is followed by cell damage (Dat et al, 1998;Han and Wang, 2002). In agreement with previous reports (Diebold et al, 2004;Herrmann et al, 2017;Lima et al, 2018), our results indicated the bentazon could interfere with Under stress conditions, plants usually generate higher levels of ROS, which subsequently induce peroxidation of membrane lipids and oxidative damage (Kar, 2011;Munn e-Bosch and Peñuelas, 2003). Melatonin is a plant growth regulator that improves photosynthetic efficiency in higher plants under stressful conditions (Jiang et al, 2016;Yin et al, 2013;Zhao et al, 2015).…”
Section: Discussionsupporting
confidence: 90%
“…This inhibition of photosynthesis and oxidative stress is followed by cell damage (Dat et al, 1998;Han and Wang, 2002). In agreement with previous reports (Diebold et al, 2004;Herrmann et al, 2017;Lima et al, 2018), our results indicated the bentazon could interfere with Under stress conditions, plants usually generate higher levels of ROS, which subsequently induce peroxidation of membrane lipids and oxidative damage (Kar, 2011;Munn e-Bosch and Peñuelas, 2003). Melatonin is a plant growth regulator that improves photosynthetic efficiency in higher plants under stressful conditions (Jiang et al, 2016;Yin et al, 2013;Zhao et al, 2015).…”
Section: Discussionsupporting
confidence: 90%
“…O estudo conduzido porLima et al (2018), sobre o potencial fotossintético e produtividade de feijão carioca sob efeito de herbicidas aplicados aos 23 dias após a emergência da cultura, demonstrou que os herbicidas bentazone, fomesafen, fluazifop-p-butil e fluazifop-p-butil+fomesafen, reduziram o número de vagens por planta, mas não influenciaram o número de grãos por vagem, peso de 100 grãos e produtividade de grãos, não corroborando, o presente trabalho. Isso se deve o fato desses herbicidas serem indicado (seletivos) para a cultura do feijão (Phaseolus vulgaris), diferentemente do feijão-caupi (Vigna unguiculata).…”
unclassified
“…Assim como ocorre em outros cultivos, sua produção pode ser influenciada por fatores como as condições climáticas e a interferência de insetos, doenças e plantas daninhas. Se não controladas, algumas dessas pragas podem causar reduções de produtividade em até 80% (LIMA et al, 2018;PORTUGAL et al, 2014).…”
Section: Introductionunclassified